Industrial Development Strategy Until 2030 - Al- Hayaly, Adel Ghazi Khalil Jasim (Journal of Economics and Administrative Sciences, 2022)
The research is a vision of the future of industry in Iraq, so it is may be outside the ceiling of the capabilities of the Iraqi economy, and therefore it is exaggerated. Therefore, future plans must be applicable through the availability of capabilities. Everyone knows that the financial and administrative corruption and mismanagement of resources are the main cause of the inefficiency of the industrial sector, and the failure to exercise its real role in achieving economic development.; as well as the political situation and the dominance of parties and their insistence on addressing positions that have a strong relationship in managing the economic sector that has a significant impact on drawing the economic map in its current form. That is why it has become necessary to reform the political system as an important pillar for the success of this strategy.It presents the vision of the industrial system until 2030, which is summarized in the development of the industrial system in Iraq to support a diversified and sustainable national economy in terms of economic and environmental aspects. It works within a stimulating business environment based on creativity and works in an institutional and organizational system that ensures implementation and achievement of goals and contributes to providing more job opportunities and improving the standard of living for individuals and society. To implement this vision, four basic elements were identified that represent the axes of the industrial strategy, namely: building the nucleus of competitive industrial clusters based on large industrial facilities integrated with local and global value chains, creating effective and stable working conditions that allow the existence and growth of private enterprises, improving the industrial and knowledge infrastructure, and adopting an appropriate governance system that supports the implementation of the previous three axes. A set of goals have been set for each of these axes to form the whole path the strategy to follow